A toolbox for steady state and transient stability analysis with MATLAB - Randel, Dana (2007)
The tendency of a power system to develop restoring forces equal or greater than the disturbing forces to maintain the state of equilibrium is known as stability. The stability problem is concerned with the behavior of the synchronous machines after a disturbance. Stability problems are divided into two major categories which is steady state stability and transient stability. In this project, the analysis will be on steady state and transient stability. The analysis of steady state is important to determine the ability of the power system to regain synchronism after small and slow disturbances. Analysis of transient stability is needed to ensure that the system can withstand the transient condition following a major disturbance. However, the manual calculation using calculator and formula and also the simulation of the steady state stability and transient stability maybe take a long time for student to understand the theory part of stability.The existence of transient and steady state toolbox will help us to create faster transient and steady state analysis. The availability of steady state and transient stability analysis toolbox package has extended classroom capabilities and enhanced student interest in power engineering courses.Therefore, a toolbox for steady state and transient stability analysis is developed. -Author